The influence of pay satisfaction, leadership and work envirement on academician's job perfomance - Nur Masyitah, Kamaruddin (2024)
It is important for a university to understand and manage issues related to academicians' job performance, as this can either increase or decrease their performance. There are several factors that would influence academicians’ job performance namely teaching quality, publication record, ethical behaviour, job commitment level, pay satisfaction, leadership style, and work environment. This paper aims at analysing the influence of pay satisfaction, leadership, and work environment on academicians’ job performance at a higher education institution in Malaysia. The research objective attempts to provide relationship between pay satisfaction, leadership, and work environment on academicians’ job performance as well as enhancing the validity and reliability of the existing research. This study employs a quantitative approach to investigate the hypothesis and identify the influence of pay satisfaction, leadership, and work environment on job performance of academicians at a private university located in Perak. Data were gathered using questionnaires collected from 142 of academicians including professor, associate professor, senior lecturer and lecturer. Descriptive analysis, reliability analysis, correlation analysis, and multiple regression analysis were used to measure the outcome between pay satisfaction, leadership, and work environment on academicians’ job performance. The findings of the study reveal that leadership and work environment were significantly correlated with and contributed in improving academicians’ job performance and the findings rejected the influence of pay satisfaction towards academicians’ job performance due to insignificantly correlated. Based on findings of the study, it is show that pay satisfaction may not always have significant influence on academicians’ job performance due to underpaid issue, weak pay increment procedure, low pay rise and pay disparities. On the other hand, academicians at the university would perform well if their leaders had an effective leadership style. In addition, a positive work environment also contributes to the improvement of job performance among academicians. In conclusion, this study found that leadership style and work environment influence academicians' job performance. The study's findings not only aid universities and the education sector, but also contribute to the broader Malaysian community.